107 Tapia's syndrome – is the mechanism neuropraxia from intubation or is it more complex?. Issue 6 (27th May 2022) - Hutchinson, Joseph; MacDonald, Bridget
Abstract : An otherwise well 23 year old lady had a septorhinoplasty with bilateral implants under general anaesthesia for nasal blockage and right sided nasal deviation. The operation was successful but six hours later the left side of her tongue felt odd, she had dysphonia and 'it felt funny to swallow'. She had deviation of the tongue to the left on protrusion; couldn't quickly it it from side to side; and the sensation on its left side was altered. There wasn't obvious tongue swelling or haematoma and no weakness or numbness in the face or limbs. Naso-endoscopy confirmed a left vocal cord paralysis. This was recognised as a left sided hypoglossal and vagal nerve palsy. The ENT and anaesthetic teams, felt that it might have been due to over-packing of the throat causing compression and neuropraxia. Her symptoms substantially improved after 5 days with a course of dexamethasone. This case will be discussed with reference to both the first described and more recent case reports of Tapia's syndrome along with the hypothesised mechanisms of injury. Tapia's syndrome is a thought to be due to pressure during intubation but most case reports follow surgeries with hammering and other sudden applications of force, rather than in emergency situations which would be expected to have more problems resulting from intubation. It seems important that those who resuscitate patients are aware of this potential complication. hut898@gmail.com